Assessment of Potential Safety Hazards and Exposure During Condenser Manufacturing Process - Syed Mirza Akmal, (Progress in Engineering Application and Technology, 2023)
A manufacturer is a manufacturer of finished goods from raw materials using a variety of tools, equipment, and processes and then sells those goods to consumers. The study reveals that the condenser manufacturing area was exposed to some hazards during the process of condenser manufacture. This includes physical hazards, ergonomic hazards, psychosocial hazards and chemical hazards. Out of 31 identified hazards, 0% posed a high-level risk, another 13% posed a medium-level risk and 87% of a low-level risk. The major hazard found was physical hazard which contributes to 67% of the medium-level risk. Finally, for the hazard, the control measures are proposed in accordance with the hierarchy of risk control (elimination, substitution, engineering control, administrative control and personal protective equipment).